2004
DOI: 10.1016/j.jmb.2004.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the RNA Degradosome-organizing Domain of the Escherichia coli Ribonuclease RNase E

Abstract: The hydrolytic endoribonuclease RNase E, which is widely distributed in bacteria and plants, plays key roles in mRNA degradation and RNA processing in Escherichia coli. The enzymatic activity of RNase E is contained within the conserved amino-terminal half of the 118 kDa protein, and the carboxy-terminal half organizes the RNA degradosome, a multi-enzyme complex that degrades mRNA co-operatively and processes ribosomal and other RNA. The study described herein demonstrates that the carboxy-terminal domain of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
208
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(241 citation statements)
references
References 54 publications
(64 reference statements)
15
208
1
1
Order By: Relevance
“…4). This contrasts with the behavior of WT RhlB and all other helicases used in the present work, which elute later and are likely to be monomers based on our current and earlier mass spectrometry data (22).…”
Section: Analysis Of Interactions Of Rhlb Surface Mutants With Rnase E-contrasting
confidence: 92%
See 4 more Smart Citations
“…4). This contrasts with the behavior of WT RhlB and all other helicases used in the present work, which elute later and are likely to be monomers based on our current and earlier mass spectrometry data (22).…”
Section: Analysis Of Interactions Of Rhlb Surface Mutants With Rnase E-contrasting
confidence: 92%
“…However, the effects of only a very few cofactors or accessory proteins on the enzymatic functions of RNA helicases have been characterized in vitro. As part of the present work we have extended previous studies that have reported on the E. coli DEAD box RNA helicase, RhlB, whose ATPase activity is stimulated by interaction with its partner protein, the endoribonuclease RNase E (19,22,23). Evidence indicates that the boost of ATPase activity is not caused by increased recruitment of RNA (18).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations